THE COMMAND TO FIGHT NON-MUSLIMS BASED ON HADITH PERSPECTIVE (THE MICRO AND MACRO ANALYSIS STUDIES) - Imran, Muhammad; Mahmud, Basri; Baba, Muammar; Taufani, Taufani (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
This study aimed at comprehending Hadiths of ‘command to fight non-Muslims’. Understanding the hadith of the Prophet PBUH by using macro and micro approaches can avoid radicalism, intolerance, and even acts of terrorism. This research employed a qualitative descriptive by using the thematic analysis method. The researchers found that, in microanalysis studies of the hadith, there were 62 riwayahs with various lafaz variants, recorded in 8 kutub al-hadis (canonical and non canonical hadiths). The Hadiths’ command to fight non-Muslims' status was authentic both from the aspect of sanad and matn. Meanwhile, the macro analysis study of the hadith concluded that the practice of the hadith command to fight Non-Muslims must be understood in certain circumstances, not the generality lafaz of hadith. Textually, the hadith ‘command to fight non-Muslims’ can be applied if; 1) non-Muslims fought openly against Islam such as in the case of the Khaibar war, or 2) they refused the invitation of monotheism from the Prophet PBUH, such us what happened to the Bani Thaqif. After they were repulsed in the battle of Hunain, they fled to the Bani Taif area. Bani Tsaqif was besieged for 40 days, some of them surrendered and pledged to Islam. But if non-Muslims did not attack Muslims, or they made agreements in one country (mu'ahad), or they had the status of conquest and control of Muslims (dhimmi), then, their blood, soul, family, and property must be protected. The position of both non-Muslims and Muslims in the country was the same, they were citizens and the government must protect them.الملخصتهدف هذه الدراسة إلى وصف فهم الأحاديث حول